MapHead - Howarth, Lesley (London : Catnip Books, 2011)
Twelve-year-old MapHead, a boy with strange powers from an alternative world, travels to England in search of his human mother.
Originally published: London : Walker Books Ltd., 1994.
Young Adult.
Young Adult
Keywords: Mothers and sons -- Fiction; Science fiction; Mothers and sons -- Fiction; Science fiction